Efektivitas Pembelajaran Matematika Model Mind Mapping dan Make A Match terhadap Kemampuan Berfikir Kritis Siswa - Machromah, Isnaeni Umi; Efendi, Muhamad Taufiq (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effectiveness of the mind mapping learning model in mathematics learning and to measure the critical thinking skills of eighth-grade students at SMP Negeri 1 Gondang. This study employed quantitative research. The research method used was a quasi-experimental method. The data sources were 64 students in grades VIII B and VIII C. The results of the data analysis indicate that the mind mapping learning model has an effect on students' critical thinking skills, as indicated by an n-gain score of 83%, which is considered high. Meanwhile, the n-gain score for the make-a-match class was 73%, which can be considered high. Conclusion: There are differences between the mind mapping and make-a-match models, with the mind mapping model having a better effect than the make-a-match model. Keywords: Mind mapping, Make a match, n-gain score